In Memoriam Ana Savić - Matić, Gordana; Kojic, Snezana (Archives of Biological Sciences, 2022)
In 2022 we celebrated half a century of the Serbian School of Molecular Biology. Molecular Biology and Physiology, as a novel study group, was founded in 1972 at the Department of Biological Sciences of the Faculty of Sciences and Mathematics, University of Belgrade. The University of Belgrade was the third university in the world to establish molecular biology studies and a department of biochemistry and molecular biology. The founder was the academician Dušan Kanazir, together with Ana Savić who was his only assistant at the time. Professor Ana Savić started her teaching career after graduating in 1961 at the Department of Physical Chemistry of the Faculty of Sciences and Mathematics at the University of Belgrade. She received her PhD in 1972, and in 1973 she was elected Assistant Professor at the newly established study program Molecular Biology and Physiology...